Patient indications for Mohs micrographic surgery: a clinical practice guideline - Murray, C. (Curr Oncol, 2019)
OBJECTIVE: The purpose of the present work was to develop evidence-based indications for Mohs micrographic surgery in patients with a diagnosis of skin cancer. METHODS: The guideline was developed by Cancer Care Ontario’s Program in Evidence-Based Care, together with the Melanoma Disease Site Group and the Surgical Oncology Program, through a systematic review of relevant literature, patient- and caregiver-specific consultation, and internal and external reviews. RECOMMENDATION 1: Given a lack of high-quality, comparative evidence, surgery (with postoperative or intraoperative margin assessment) or radiation (for those who are ineligible for surgery) should remain the standard of care for patients with skin cancer. RECOMMENDATION 2: Mohs micrographic surgery is recommended for patients with histologically confirmed recurrent basal cell carcinoma of the face and is appropriate for primary basal cell carcinomas of the face that are larger than 1 cm, have aggressive histology, or are located on the H zone of the face. RECOMMENDATION 3: Mohs micrographic surgery should be performed by physicians who have completed a degree in medicine or equivalent, including a Royal College of Physicians and Surgeons of Canada Specialist Certificate or equivalent, and have received advanced training in Mohs micrographic surgery.